Subversion of Lipopolysaccharide Signaling in Gingival Keratinocytes via MCPIP-1 Degradation as a Novel Pathogenic Strategy of Inflammophilic Pathobionts - Anna Gasiorek (American Society for Microbiology, 2021)
Periodontitis is a highly prevalent disease caused by accumulation of a bacterial biofilm. Periodontal pathogens use a number of virulence strategies that are under intensive study to find optimal therapeutic approaches against bone loss.